Influencing factors and prognostic value of left ventricular systolic dysfunction in patients with complete occlusion of the left anterior descending artery reperfused by primary percutaneous coronary intervention - Yongle Jing; Chengzhi Lu; Suzhen Guo; Bingwei Chen; Xuying Ye; Qiang He; Wei Xia; Ting Xin (BMC Cardiovascular Disorders, 2023)
Abstract Background The aim of this study was to perform a retrospective analysis of patients with acute anterior wall ST-segment elevation myocardial infarction (AAW-STEMI) whose left anterior descending (LAD) artery was completely occluded and reperfused by primary percutaneous coronary intervention (PPCI) and to determine the influencing factors and prognostic value of left ventricular systolic dysfunction (LVSD) in the acute phase of acute myocardial infarction (AMI). Methods A total of 304 patients with AAW-STEMI were selected. The selected patients were divided into two groups: the preserved left ventricular ejection fraction (pLVEF) group (LVEF ≥ 50%, n = 185) and the reduced left ventricular ejection fraction (rLVEF) group (LVEF < 50%, n = 119). The influencing factors of LVSD and their predictive value for LVSD were analyzed. Patients were followed up by examining outpatient records and via telephone. The predictive value of LVSD for the cardiovascular mortality of patients with AAW-STEMI was analyzed. Results Age, heart rate (HR) at admission, number of ST-segment elevation leads (STELs), peak creatine kinase (CK) and symptom to wire-crossing (STW) time were independent risk factors for LVSD (P < 0.05). The receiver operating characteristic (ROC) analysis showed that the peak CK had the strongest predictive value for LVSD, with an area under the curve (AUC) of 0.742 (CI, 0.687 to 0.797) as the outcome. At a median follow-up of 47 months (interquartile range, 27 to 64 months), the Kaplan‒Meier survival curves up to 6-year follow-up revealed a total of 8 patients succumbed to cardiovascular disease, with 7 (6.54%) in the rLVEF group and 1 (0.56%) in the pLVEF group, respectively (hazard ratio: 12.11, [P = 0.02]). Univariate and multivariate Cox proportional hazards regression analysis demonstrated that rLVEF was an independent risk predictor of cardiovascular death in patients with AAW-STEMI discharged after PPCI (P < 0.01). Conclusions Age, HR at admission, number of STELs, peak CK, and STW time may be used to identify patients with a high risk of heart failure (HF) in a timely manner and initiate early standard therapy for incident LVSD in the acute phase of AAW-STEMI reperfused by PPCI. A trend toward increased cardiovascular mortality at follow-up was significantly linked to LVSD.